The Influence of Economic Literacy and Lifestyle on the Consumptive Behavior of Students - Ahmad Bachtiar Firdaus; Luthfiya Fathi Pusposari (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2022)
This research aims to analyze the effect of economic literacy and life style on consumer behavior social science student who has active as student social science UIN Malang at 2019 grade. This research is quantitative research. The data collection techniques using questionnaires. The population is 108 students, and use 85 students as samples which elected by proportional random sampling. this research was analyzed using multiple linier regression. The results of the study are (1) economics literacy has significant negative effect on customer behavior (2) live style has significant positive effect on consumptive behavior (3) economics literacy and live style have positive effect on consumptive behavior.